8D.03: EVIDENCE FOR AN ACE-INDEPENDENT TISSUE-SPECIFIC RAS REGULATION AFTER KIDNEY TRANSPLANTATION. (June 2015) - Kovarik, J.J.; Kaltenecker, C.C.; Domenig, O.; Kopecky, C.; Antlanger, M.; Poglitsch, M.; Kain, R.; Eskandary, F.; Böhmig, G.A.; Säemann, M.D.
Abstract : Objective: Angiotensin-converting enzyme inhibitors (ACEis) are beneficial in patients with chronic kidney disease, yet their effects in kidney transplant (TX) recipients remain inconclusive. Allograft quality, transplant vintage and donor-specific antibodies (DSA) might constitute crucial factors, leading to dysregulation of the intrarenal RAS and altered sensitivity to RAS blocking agents such as ACEis. Here, we investigated local angiotensin metabolism in transplant recipients with varying graft vintage, compared to healthy living donors as controls to assess graft specific and time-dependent changes of RAS effector angiotensin (Ang) II and Ang 1-7 formation rates. Design and method: In this cross-sectional, single center, exploratory study, 30 kidney biopsies of DSA-positive (BORTEJECT study) and 30 DSA-negative allograft recipients (both groups ACEi treatment vs. no RAS blockade), as well as healthy living kidney donors (n = 5) were used for analyzing intrarenal RAS activity by a highly sensitive mass spectrometry-based assay. Employing selective enzyme inhibitors during ex vivo incubation of biopsy homogenates after Ang I substrate spiking, we investigated ACE and chymase mediated Ang II formation. Respectively, we assessed neprilysin (NEP) and prolyl endopeptidase (PEP)-mediated Ang 1–7 formation from Ang I, as well as ACE2 and prolyl carboxypeptidase (PCP)-mediated Ang 1–7 formation after Ang II spiking. In parallel, we performed immunohistochemical (IHC) renal RAS enzyme stainings. Additionally, we simultaneously quantified multiple systemic angiotensin levels of all patients. Results: We found increased local Ang II to Ang 1–7 ratios with higher TX vintage in transplant recipients with and without ACEi-treatment. Compared to samples of healthy kidneys, we found a high proportion of ACE-independent Ang II formation rates in biopsies of transplanted patients. Surprisingly, our results revealed that NEP but not ACE2 or PCP is the key Ang 1–7 forming enzyme in transplanted renal tissue independent of TX vintage. Conclusions: The close association between increased renal Ang II formation rate and the TX vintage, which was independent of ACEi therapy, indicates a profoundly altered local sensitivity to ACEis. Our finding that NEP is the key Ang 1–7-forming enzyme in kidney allografts may have considerable implications for future RAS interfering therapies.